63.6k views
4 votes
Let g(x) = cot(2).

Find g
(6)
Choose 1 answer:
2
B
0
-2
D
1

Let g(x) = cot(2). Find g (6) Choose 1 answer: 2 B 0 -2 D 1-example-1
User Prydie
by
5.6k points

1 Answer

4 votes

Answer:

C. -2

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Algebra I

  • Function Notation

Pre-Calculus

  • Unit Circle

Calculus

  • Derivatives
  • Derivative Notation
  • Derivative of cot(x) = -csc²(x)

Explanation:

Step 1: Define

g(x) = cot(x)

g'(π/4) is x = π/4

Step 2: Differentiate

  1. Differentiate: g'(x) = -csc²(x)

Step 3: Evaluate

  1. Substitute in x: g'(π/4) = -csc²(π/4)
  2. Evaluate: g'(π/4) = -2
User Imran Qasim
by
5.9k points